A realist approach to understanding alliancing within Local Government public health and social care service provision. (1st December 2022) - Redgate, S; Spencer, L; Adams, E A; Arnott, B; Brown, H; Christie, A; Hardy, C; Harrison, H; Kaner, E; Mawson, C; McGovern, W; Phillips, P; et al.
Abstract: Background: Within the current context of continued austerity and post-pandemic recovery, it remains important that Local Government services address the increasing needs of residents as cost-effectively as possible. Alliancing, whereby services work collaboratively focusing on the 'whole-system', has gained popularity as a tool with the potential to support collaborative whole systems approaches. This synthesis aims to identify how alliancing can be successfully operationalised in the commissioning of public health, wider National Health Service (NHS) and social care-related services. Methods: A realist literature synthesis was undertaken in order to identify underlying generative mechanisms associated with alliancing, the contextual conditions surrounding the implementation and operationalisation of the alliancing approach mechanisms, and the outcomes produced as a result. An iterative approach was taken, using a recent systematic review of the effectiveness of Alliancing, online database searches, and grey literature searches. Results: Three mechanistic components were identified within the data as being core to the successful implementation of alliances in public health and social care-related services within Local Government: (i) Achieving a system-level approach; (ii) placing local populations at the heart of the system; and (iii) creating a cultural shift. Programme theories were postulated within these components. Conclusions: The alliancing approach offers an opportunity to achieve system-level change with the potential to benefit local populations. The realist synthesis approach taken within this study has provided insights into the necessary contextual and mechanistic factors of the Alliancing approach, above and beyond effectiveness outcomes typically collected through more conventional evaluation methodologies.